PENGELOLAAN SAMPAH BERKELANJUTAN MELALUI INOVASI TEMPAT SAMPAH ONE-PART GEOPOLYMER DARI LIMBAH SERBUK ANDESIT DI DESA PANDEAN, NGANJUK - Handayani, Agil; Endang Mei Yunalia; Mega Septia Sarda Dewi (Jurnal Abdi Masyarakat, 2025)
The village of Pandean in Nganjuk Regency faced significant river pollution along a 1.8 km stretch due to waste accumulation, stemming from low public awareness and a lack of proper waste facilities. This community service program was implemented to address this by increasing environmental awareness and establishing a sustainable waste management system. The program involved three stages: preparation, implementation, and evaluation. Key outputs included the creation and strategic placement of five one-part geopolymer trash bins, five plastic bottle separators, and one portable trash bin. Educational activities targeting housewives and students successfully increased environmental knowledge, with test scores improving from 54 to 84. A one-month follow-up showed positive results: 85% of residents reported better waste discipline, and 74% felt motivated to separate waste, demonstrating the program's effectiveness in integrating eco-friendly technology with community education.